2004
DOI: 10.1021/ja035730w
|View full text |Cite
|
Sign up to set email alerts
|

Charge Separation in DNA via Consecutive Adenine Hopping

Abstract: Charge transfer in DNA is of current interest because of the involvement of charge transfer in oxidative DNA damage and electronic molecular devices. We have investigated the charge separation process via the consecutive adenine (A)-hopping mechanism using laser flash photolysis of DNA conjugated with naphthaldiimide (NDI) as an electron acceptor and phenothiazine (PTZ) as a donor. Upon the 355-nm laser flash excitation of NDI, the charge separation and recombination process between NDI and PTZ was observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
202
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(230 citation statements)
references
References 41 publications
22
202
6
Order By: Relevance
“…In many experiments characterizing DNA CT, a shallow distance dependence in the reaction has been demonstrated (1)(2)(3)(4)(5)(6)(7)(8), and this shallow distance dependence has been explained through models primarily involving long-range diffusive charge-hopping (15,16,34). Models involving a mixture of hopping among low-energy guanine sites and tunneling through AT tracts provided a useful starting point for reconciling many experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many experiments characterizing DNA CT, a shallow distance dependence in the reaction has been demonstrated (1)(2)(3)(4)(5)(6)(7)(8), and this shallow distance dependence has been explained through models primarily involving long-range diffusive charge-hopping (15,16,34). Models involving a mixture of hopping among low-energy guanine sites and tunneling through AT tracts provided a useful starting point for reconciling many experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Models involving a mixture of hopping among low-energy guanine sites and tunneling through AT tracts provided a useful starting point for reconciling many experiments. Once experiments demonstrated rapid, long-range DNA CT across assemblies containing adenine tracts (5,7,34,35), the model was modified to include also hopping on low-energy adenines (18). These models, however, consistently explain DNA CT in the context solely of base energetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosecond transient absorption measurements were performed by using the LFP technique (31,35). The third-harmonic oscillation (355 nm, full width at half maximum of 4 ns, 20 mJ per pulse) from a Q-switched neodymium-doped yttrium aluminum garnet (Nd:YAG) laser (Surelight, Continuum, Santa Clara, CA) was used to excite the NI site selectively because NI showed strong absorption around 355 nm ( 355 Ϸ 8 ϫ 10 3 M Ϫ1 ⅐cm Ϫ1 ) and PTZ showed no absorption at wavelengths longer than 320 nm (32). A xenon flash lamp (XBO-450, Osram, Berlin) was focused into the sample solution as the probe light for the transient absorption measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we demonstrated that the adenine hopping (Ahopping) occurred very rapidly (Ͼ10 8 s Ϫ1 ) and can be applied to generate a long-lived charge-separated state in DNA (31,32). Accordingly, it is expected that a long-lived hole escaped from charge recombination can be generated effectively in DNA by using the A-hopping mechanism, which enables us to observe the hole-transfer process occurring in the much slower time scale.…”
mentioning
confidence: 99%